CIFC - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Portugal's Centro de Investigação das Ferrugens do Cafeeiro (Centre for Research into Coffee Rusts) was created in 1955, as part of the Instituto de Investigação Científica Tropical (Institute for Tropical Scientific Research) with the aim of...